UCP4C mediates uncoupled respiration in larvae of Drosophila melanogaster. - Da-Ré, C.; De Pittà, C.; Zordan, M.A.; Teza, G.; Nestola, F.; Zeviani, M.; Costa, R.; Bernardi, P. (EMBO Reports, 2014)
Larvae of Drosophila melanogaster reared at 23°C and switched to 14°C for 1 h are 0.5°C warmer than the surrounding medium. In keeping with dissipation of energy, respiration of Drosophila melanogaster larvae cannot be decreased by the F-ATPase inhibitor oligomycin or stimulated by protonophore. Silencing of Ucp4C conferred sensitivity of respiration to oligomycin and uncoupler, and prevented larva-to-adult progression at 15°C but not 23°C. Uncoupled respiration of larval mitochondria required palmitate, was dependent on Ucp4C and was inhibited by guanosine diphosphate. UCP4C is required for development through the prepupal stages at low temperatures and may be an uncoupling protein.